5x + x - 6x + 2x = 2x
5x+15 = 6x-10 5x-6x = -10-15 -x = -25 x = 25
6x + 3 = -7 -5x 6x + 5x = -7 -3 11x = -10 x = -10/11
5x+3+x=24 6x+3=24 6x=21 x=3.5
6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.
5x + x - 6x + 2x = 2x
-6x+3 = -7-5x 7+3 = 6x-5x 10=x
5x+15 = 6x-10 5x-6x = -10-15 -x = -25 x = 25
-5x+1 = 6x -5x-6x = -1 -11x = -1 x = 1/11
2(1 - 3x + 6) = -x 14 - 6x = -x 14 - 6x + 6x = -x + 6x 14 = 5x 14/5 =5x/5 14/5 = x
(9,2)
6x + 3 = -7 -5x 6x + 5x = -7 -3 11x = -10 x = -10/11
5x+3+x=24 6x+3=24 6x=21 x=3.5
6x-x+15-9= 6x-x=5x 15-9=6 5x+6=0 5x=-6 x=-1.2
5x + 4 = 6x - 2Add 2 to each side of the equation:5x + 6 = 6xSubtract 5x from each side:6 = x
5x + 3 = 6x + 1 Subtract 5x from both sides: 3 = x + 1 Subtract 1 from both sides: 2 = x
6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.